Sea surface temperature anomaly in the coastal waters of Vietnam related to ENSO phenomenon - Tac, Vu Van; Huan, Nguyen Huu; Son, Tong Phuoc Hoang; Tien, Manh Manh; Khang, Nguyen Hoang Thai; Quang, Phan; Chung, Tran Van (Vietnam Journal of Marine Science and Technology, 2020)
The studies on the impact of the ENSO phenomenon on climate and environment change have shown that the Bien Dong (Southeast Asia Sea) is strongly influenced by this phenomenon. This paper focuses on analyzing sea surface temperature (SST) monthly data for 16 years (7/2002–12/2017) in the coastal waters of Vietnam from MODIS satellite images of National Aeronautics and Space Administration (US NASA). The analysis results showed a clear pattern of ENSO impacts on SST in the coastal waters of Vietnam. However, the intensity of the ENSO phenomenon affecting the three studied areas is very different, and in terms of trend, the intensity gradually increases to the north. The period of impact of ENSO on SST in the coastal waters of Vietnam is often about one month later than the ONI index and the influenced duration lasts about 6 to 9 months. In addition, in the La Niña years, the values of the SST anomaly reflect quite well in terms of the intensity of the La Niña phenomenon. However, in the El Niño years, the SST anomaly index is not generally proportional to the ONI index. Specifically, in the years when El Niño phenomenon was considered to be weak, the SST anomaly index of the coastal waters of Vietnam is much higher than in the years when El Niño phenomenon was considered to be moderate or very strong. The above results are contributing to improving the understanding of the impact of the vagaries of the climate on the coastal waters of Vietnam, supporting scientists and managers in making measures to prevent and efficiently avoid, limit and mitigate the damage caused by ENSO, and to have reasonable alternatives in the protection of biodiversity and environment in the coastal waters of Vietnam. It could be considered as a “small piece” of the overall picture of the impacts of the ENSO phenomenon on global climate change